EVALUASI IMPLEMENTASI BI’AH LUGHAWIYYAH DALAM PENGEMBANGAN MAHĀRAH AL-KALĀM SANTRI PEMULA DI PESANTREN MAWARIDUSSALAM - Ginting, Zulkifli Ismail; Setiyadi, Alif Cahya; Najib, Ahmad Farhan Rif'an (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The language environment, or bi’ah lughawiyyah, is a crucial element in second language acquisition, particularly speaking skills. However, its management in many Islamic boarding schools is often inconsistent and lacks systematicity. This study focuses on evaluating the implementation of bi’ah lughawiyyah at the Mawaridussalam Islamic Boarding School in Deli Serdang and analyzing its contribution to the speaking skills of novice students. Using a qualitative case study approach, the research stages include participant observation, semi-structured interviews, and documentation, with data analysis techniques based on the Miles and Huberman model. The research findings reveal that the implementation of the language environment is carried out through a structured system supported by a hierarchical driving organization, involving teachers and student organizations. Featured programs include ilqā’ al-mufradāt (learning to read and understand the language), disciplinary control through the Language Court, and expressive activities such as the Arabic Club and Language Expo. The integration of organizational structure, communication habits, and strict supervision creates an active and consistent communication ecosystem. The main conclusion confirms that systematically managed bi'ah lughawiyyah provides an intensive practice space for novice students to interact using Arabic in everyday life. The success of this model lies in the synergy between disciplinary regulations and creative activities that motivate students to speak freely. Thus, this language ecosystem provides a strong foundation for accelerating students' speaking skills from an early age in an effective, comprehensive, and sustainable manner within the Islamic boarding school environment, supporting the quality of their communicative competence. ABSTRAK Lingkungan bahasa atau bi’ah lughawiyyah merupakan elemen krusial dalam pemerolehan bahasa kedua, khususnya keterampilan berbicara, namun pengelolaannya di banyak pesantren sering kali tidak konsisten dan kurang sistematis. Penelitian ini berfokus mengevaluasi implementasi bi’ah lughawiyyah di Pesantren Mawaridussalam Deli Serdang serta menganalisis kontribusinya bagi kemampuan berbicara santri pemula. Menggunakan pendekatan kualitatif studi kasus, tahapan penelitian meliputi observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi, dengan teknik analisis data model Miles dan Huberman. Temuan penelitian mengungkapkan bahwa implementasi lingkungan bahasa dilaksanakan melalui sistem terstruktur yang didukung organisasi penggerak berjenjang, melibatkan guru dan organisasi santri. Program unggulan mencakup ilqā’ al-mufradāt, muhādatsah, kontrol disiplin melalui Mahkamah Bahasa, serta kegiatan ekspresif seperti Arabic Club dan Language Expo. Integrasi antara struktur organisasi, pembiasaan komunikasi, dan pengawasan ketat menciptakan ekosistem komunikasi yang aktif dan konsisten. Simpulan utama menegaskan bahwa bi’ah lughawiyyah yang dikelola secara sistematis memberikan ruang praktik intensif bagi santri pemula untuk berinteraksi menggunakan bahasa Arab dalam keseharian. Keberhasilan model ini terletak pada sinergi antara regulasi disiplin dan kegiatan kreatif yang memotivasi santri berbicara tanpa beban. Dengan demikian, ekosistem bahasa ini menjadi fondasi kuat dalam mengakselerasi kemahiran berbicara santri sejak dini secara efektif, komprehensif, dan berkelanjutan di lingkungan lembaga pendidikan pesantren tersebut guna menunjang kualitas kompetensi komunikatif mereka.